Konflikt, integration og parlamentarisk kultur i Den Grundlovgivende Rigsforsamling 1848-49 - Riisager, Niels (Historisk Tidsskrift, 2025)
Conflict, integration and parliamentary culture in the Danish Constituent Assembly 1848-49 The predominant narratives of the Danish constitutional transition from Absolutism to constitutional monarchy in 1848-49 can broadly be divided into an older tradition depicting the process as fundamentally consensus-driven and peaceful, and more recent accounts that have highlighted conflicting ideas, concepts, and events in the process leading up to the Liberal June Constitution 1849 (Junigrundloven). So far, little has been done to synthesize the two perspectives, i.e. to answer the question, how contemporaries, in the face of serious social and political divisions, succeeded in passing a new constitution. The present study asks, first, how the members of the Danish Constituent Assembly (Den Grundlovgivende Rigsforsamling) conceptualized the parliamentary process and, second, with what consequences for the mediation of conflict in the assembly. By introducing an analytical distinction between integrative concepts and contestative concepts, the study highlights the performative impact of parliamentary concepts and, by extension, of parliamentary culture on the constitutional transition. It argues that the conceptualization of the parliamentary process was dominated by a set of deliberative concepts – namely the concepts of deliberation (Diskussion/Overveielse) and the concepts of conviction (Mening/Anskuelse/Overbeviisning) – and that these concepts, despite some instances of semantic conflict, possessed a fundamentally integrative function in the deliberations of the Constituent Assembly, thus, mediating the significant conflict potential at hand. In fact, the biggest challenge to the deliberative concepts did not arise because of interpretive conflict, but as a consequence of an integrational crisis at the height of deliberations in March 1849. The result of the crisis was the consolidation of a certain interpretation of the deliberative concepts – referred to as the composite concept of conviction – rendering their integrative force nearly intact.